Preliminary Study of In Vivo Formed Dental Plaque Using Confocal Microscopy and Scanning Electron Microscopy - KA. Al-Salihi; NABA. Tarmidzi (Tehran University of Medical Sciences, 2009)
Objective: Confocal laser scanning microscopy (CLSM) is relatively a new light microscopical imaging technique with a wide range of applications in biological sciences. primary value of CLSM for the biologist is its ability to provide optical sections from three-dimensional specimen. The present study was designed to assess the thickness content of in vivo accumulated dental plaque using CLSM and scanning electron microscopy (SEM). Materials and Methods: Acroflat lower arch splints (acrylic appliance) were worn five participants for three days without any disturbance. The formed plaques were assessed using CLSM combined with vital fluorescence technique and SEM. Results: In this study accumulated dental plaque revealed varied plaque microflora vitality and thickness according to participant's oral hygiene. The thickness of plaque smears ranged from 40.32 to 140.72 µm and 65.00 to 128.88 µm for live (vital) and dead accumulated microorganisms, respectively. Meanwhile, the thickness of plaque on the appliance ranged from 101 µm to 653 µm. CLSM revealed both dead and vital bacteria on the surface of the dental plaque. In addition, SEM revealed layers of various bacterial aggregations in all dental plaques. Conclusion: This study offers a potent non-invasive tool to evaluate and assess the dental plaque biofilm, which is a very important factor in the development of dental caries.